Improvement of quality of life following 6 months of methadone maintenance therapy in Malaysia - Nizam Baharom; Mohd Rohaizat Hassan; Norsiah Ali; Shamsul Azhar Shah (BioMed Central Ltd, 2024)
Indexed by Scopus